2021
DOI: 10.3390/cancers13112636
|View full text |Cite
|
Sign up to set email alerts
|

New DNA Methylation Signals for Malignant Pleural Mesothelioma Risk Assessment

Abstract: Malignant pleural mesothelioma (MPM) is a rare and aggressive neoplasm. Patients are usually diagnosed when current treatments have limited benefits, highlighting the need for noninvasive tests aimed at an MPM risk assessment tool that might improve life expectancy. Three hundred asbestos-exposed subjects (163 MPM cases and 137 cancer-free controls), from the same geographical region in Italy, were recruited. The evaluation of asbestos exposure was conducted considering the frequency, the duration and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We previously observed DNAm biomarkers in MPM patients 11,13 : among them only cg01521397 in TAF4 gene is differentially hypomethylated in preclinical samples (as well as in MPM patients), but with any significant changes closer to MPM diagnosis. The meaning of this results is interesting in the context of biomarkers reverse causality interpretation, discriminating biomarkers related to the presence of MPM from those associated to prediagnostic biological changes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We previously observed DNAm biomarkers in MPM patients 11,13 : among them only cg01521397 in TAF4 gene is differentially hypomethylated in preclinical samples (as well as in MPM patients), but with any significant changes closer to MPM diagnosis. The meaning of this results is interesting in the context of biomarkers reverse causality interpretation, discriminating biomarkers related to the presence of MPM from those associated to prediagnostic biological changes.…”
Section: Discussionmentioning
confidence: 97%
“…We aimed to assess whether previously reported DNAm biomarkers in MPM patients at diagnosis 11,13 are also informative in DNA blood samples taken up to 5 years before MPM diagnosis. To do this, we performed a multiple regression model on MESO_5YRS dataset of DNAm biomarkers previously identified as differentially methylated in a case/control study (Table S9).…”
Section: Dnam Diagnostic Biomarkers Changes In Prediagnostic Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this Special Issue, 168 authors representing 71 affiliations from 13 countries over three continents have made 19 contributions, and it is a great privilege and pleasure for the editors to introduce this collective work which summarizes important insights in this field of research. As MM is mostly related to genetic and epigenetic alterations caused by prolonged exposure to asbestos fibers, in the search for a noninvasive prognosis test, Cugliari et al showed the potential predictive value of DNA methylation changes in white blood cells as a MM survival biomarker [ 1 ], and investigated differences between MM cases and asbestos-exposed cancer-free controls [ 2 ]. Another important question concerns the discrimination between MM and benign proliferation of mesothelial cells (also frequently treated by surgery), for which Shresta et al propose a genomic differential characterization [ 3 ].…”
mentioning
confidence: 99%